Expansion of tumor-infiltrating lymphocytes (TIL) from human pancreatic tumors. Issue 1 (18th October 2016) - Hall, MacLean; Liu, Hao; Malafa, Mokenge; Centeno, Barbara; Hodul, Pamela J.; Pimiento, José; Pilon-Thomas, Shari; Sarnaik, Amod A.
Abstract : Background: We evaluated whether tumor infiltrating lymphocytes (TIL) could be expanded from surgically resected tumors from pancreatic cancer patients. Methods: Tumors were resected from pancreatic cancer patients. Tumors were minced into fragments and cultured in media containing high dose interleukin-2 (IL-2) for up to 6 weeks. T cell phenotype, activation markers, and reactivity were measured. Results: TIL expansion was measured in 19 patient samples. The majority of these TIL were CD4 + T cells and were highly activated. Purified CD8 + T cells produced IFN-γ in response to HLA-matched pancreatic tumor targets. PD-1 blockade and 4-1BB stimulation were demonstrated as effective strategies to improve effective TIL yield, including the production of tumor-reactive pancreatic TIL. Conclusions: TIL expanded from pancreatic tumors are functional and able to respond to pancreatic tumor associated antigens. PD-1 blockade, 41BB stimulation, and CD8 + T cell enrichment are effective strategies to improve TIL yield and tumor reactivity. These results support the development of adoptive cell therapy strategies using TIL for the treatment of pancreatic cancer.